A Phenotyping Tool for Seven Cytochrome P450 Enzymes and Two Transporters: Application to Examine the Effects of Clopidogrel and Gemfibrozil - Aurinsalo, Laura; Lapatto-Reiniluoto, Outi; Kurkela, Mika; Neuvonen, Mikko; Kiiski, Johanna I.; Niemi, Mikko; Tornio, Aleksi; Backman, Janne T. (Wiley, 2025)
Clinical cocktails for cytochrome P450 (CYP) phenotyping lack a marker for CYP2C8. We aimed to combine the CYP2C8 index drug repaglinide with the Geneva cocktail (caffeine/CYP1A2, bupropion/CYP2B6, flurbiprofen/CYP2C9, omeprazole/CYP2C19, dextromethorphan/CYP2D6, and midazolam/CYP3A4). We also included endogenous organic anion transporting polypeptide (OATP) 1B1 and 1B3 biomarkers glycochenodeoxycholate 3-O-glucuronide and glycochenodeoxycholate 3-sulfate, and investigated the CYP2C8 inhibition selectivity of clopidogrel and gemfibrozil with the full cocktail. In a five-phase randomized cross-over study, the following drugs were administered to 16 healthy volunteers: (i) repaglinide, (ii) the Geneva cocktail, (iii) repaglinide with the Geneva cocktail (full cocktail), (iv) clopidogrel followed by the full cocktail, and (v) gemfibrozil followed by the full cocktail. The Geneva cocktail increased repaglinide AUC(0-23h) 1.22-fold (90% confidence interval 1.04-1.44, P = 0.033). The full cocktail accurately captured known inhibitory effects of clopidogrel on CYP2B6, CYP2C8, and CYP2C19 and that of gemfibrozil on CYP2C8. Gemfibrozil decreased the paraxanthine/caffeine AUC(0-12h) ratio by 23% (14-31%, P < 0.01) and increased caffeine AUC(0-12h) 1.20-fold (1.03-1.40, P = 0.036). Gemfibrozil increased the metabolite-to-index drug AUC(0-23h) ratios of flurbiprofen, omeprazole, dextromethorphan, and midazolam 1.59-fold (1.32-1.92), 1.47-fold (1.34-1.61), 1.79-fold (1.23-2.59), and 2.1-fold (1.9-2.4), respectively, without affecting the index drug AUCs (P < 0.01). Gemfibrozil increased the AUC(0-4h) of glycochenodeoxycholate 3-O-glucuronide 1.33-fold (1.07-1.65, P = 0.027). In conclusion, the combination of repaglinide, the Geneva cocktail and endogenous biomarkers for OATP1B1 and OATP1B3 yields a nine-in-one phenotyping tool. Apart from strong CYP2C8 inhibition, gemfibrozil weakly inhibits CYP1A2 and OATP1B1 and appears to impair the elimination of the metabolites of several CYP index drugs.